Assessment of energy storage technologies: A review. (1st November 2020) - Rahman, Md Mustafizur; Oni, Abayomi Olufemi; Gemechu, Eskinder; Kumar, Amit
Highlights: Techno-economic and life cycle assessments of energy storage systems were reviewed. The levelized cost of electricity decreases with increase in storage duration. Efficiency, lifetime, and duration of discharge influence the final costs and emissions. A consistent system boundary is crucial for conducting life cycle assessment. An integrated techno-economic and life cycle assessment model is recommended. Abstract: Incorporating renewables in the power grid has challenges in terms of the stability, reliability, and acceptable operation of the power system network. One possible solution is to integrate an energy storage system with the power network to manage unpredictable loads. The implementation of an energy storage system depends on the site, the source of electrical energy, and its associated costs and the environmental impacts. Moreover, an up-to-date database with cost numbers, energy use, and resulting emissions is required for decision-making purposes. This paper reviews the techno-economic and environmental assessments of mechanical, electro-chemical, chemical, and thermal to give an update on recent developments and generate a relevant database for costs and emissions. We reviewed 91 publications, 58 on techno-economic assessment and 33 on life cycle assessment. We found that, because of economies of scale, the levelized cost of energy decreases with an increase in storage duration. In addition, performance parameters such as round-trip efficiency, cycle life, and cycle length highly influence the final costs and environmental footprints of various storage technologies. However, further research is required to build a bottom-up model that can handle all the technical parameters to quantify the levelized cost of energy and environmental footprints of the storage systems simultaneously.